2022
DOI: 10.1097/mph.0000000000002445
|View full text |Cite
|
Sign up to set email alerts
|

Late Toxicity After 3-Dimensional External Beam Radiotherapy Among Children With Cancer: A Systematic Review

Abstract: add state sales tax. The GST tax of 7% must be added to all orders shipped to Canada. (Wolters Kluwer Health, Inc., GST Identification #895524239. Publications Mail Agreement #1119672). Subscription prices outside the United States must be prepaid. Prices subject to change without notice. Visit us online at www.lww.com.Please indicate in-training status and name of institution. Institutional rates apply to libraries, hospitals, corporations, and partnerships of three or more individuals. Prices subject to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Because of this difference in dose distribution, insight in late adverse events following 3D‐RT is important. Our recent systematic literature review of observational studies on adverse health outcomes after 3D‐RT included 13 studies, most of which describe small patient cohorts (range of N : 5–246) with a median follow‐up of 8.8 years, 22 and showed that evidence on this topic is scarce. Most available studies to date reported on selected late health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of this difference in dose distribution, insight in late adverse events following 3D‐RT is important. Our recent systematic literature review of observational studies on adverse health outcomes after 3D‐RT included 13 studies, most of which describe small patient cohorts (range of N : 5–246) with a median follow‐up of 8.8 years, 22 and showed that evidence on this topic is scarce. Most available studies to date reported on selected late health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although small studies on specific childhood cancer types have reported on side effects of 3D-RT, 21 large-scale observational studies including follow-up of patients beyond the 5-year survival mark are rare to date. 22 This study has expanded upon the resources of the Dutch Childhood Cancer Survivor Study (DCCSS) LATER Cohort of 5-year CCS 10,11,23 with the purpose of filling this evidence gap. In particular, the overall aim of the Dutch Pediatric 3D-RT study is to evaluate adverse late health outcomes among children treated with radiotherapy in the era of CT-based treatment planning, and to assess dose response relationships for selected health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23] La mayoría de los efectos secundarios son auto limitados (resuelven al disminuir el edema tisular), pero algunos efectos pueden ser tardíos o permanentes, como fibrosis, infertilidad o segundas malignidades. 19,20,24,25 Actualmente, aproximadamente el 98% de los niños con LLA alcanzan remisión con tratamiento y la sobrevida a 5 años ronda el 90%; 9,26 sin embargo, se ha descrito que hasta un 20% de los niños con LLA recaen. 11 En Costa Rica se han publicado estudios acerca del diagnóstico y tratamiento de la leucemia en población pediátrica, pero ninguno específico acerca del uso de radioterapia en el tratamiento de la LLA.…”
Section: Fecha Recibido: 04 De Julio 2022unclassified